2019
DOI: 10.1371/journal.pone.0213571
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary medical male circumcision (VMMC) for prevention of heterosexual transmission of HIV and risk compensation in adult males in Soweto: Findings from a programmatic setting

Abstract: Background Clinical trials have clearly shown a reduction in HIV acquisition through voluntary medical male circumcision (VMMC). However, data assessing risk compensation under programmatic conditions is limited. Methods This was a prospective cohort of HIV seronegative males aged 18–40 years receiving VMMC between November 2012 and July 2014. HIV serostatus was determined pre and post VMMC. Risk compensation was defined as a decrease in condom use at last sex act and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…34 Besides the direct impact of MC on the reduction of HIV acquisition, MC could also generate secondary benefits by affecting the sexual behaviour of circumcised men. 35 For example, circumcised men tend to be concerned more about partner’s HIV status and to use condoms more frequently compared with non-circumcised men in South Africa. 35 Likewise, poverty was also a significant explanatory variable associated with the spatial structure of HIV for both men and women.…”
Section: Discussionmentioning
confidence: 99%
“…34 Besides the direct impact of MC on the reduction of HIV acquisition, MC could also generate secondary benefits by affecting the sexual behaviour of circumcised men. 35 For example, circumcised men tend to be concerned more about partner’s HIV status and to use condoms more frequently compared with non-circumcised men in South Africa. 35 Likewise, poverty was also a significant explanatory variable associated with the spatial structure of HIV for both men and women.…”
Section: Discussionmentioning
confidence: 99%
“…While these measures are a potential measure of service quality, this is also challenging, as individual clients may opt-out of these services, and 100% uptake on either of these measures might indicate coercive or nonoptional uptake. Further, despite the lack of studies quantifying uptake of counseling during VMMC, relationships between VMMC, counseling, and risk compensation have been assessed substantially in the literature; evidence indicates that VMMC leads to little or no risk compensation in sub-Saharan Africa [54][55][56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Our overall findings are consistent with previous reports from South Africa showing little to no evidence of risk compensation following VMMC. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about how sexual behaviour changes in real-world settings, as there have been only two studies that examined men’s sexual behaviours before and after undergoing VMMC. 13 , 14 Although the two studies, both conducted in South Africa, found minimal or no evidence of risk compensation, no studies have examined risk compensation in Botswana, where the rate of multiple and concurrent sexual partnerships is particularly high. Recently published findings from a large population-based sample found that 31% of sexually active adults in Botswana had concurrent sexual partners in the past year.…”
Section: Introductionmentioning
confidence: 99%